Kilohertz organic complementary inverters driven by surface-grafting conducting polypyrrole electrodes. (September 2016) - Zhang, Xi; Zhang, Suna; Li, Liqiang; Chen, Xiaosong; Xu, Zeyang; Wu, Kunjie; Li, Hongwei; Meng, Yancheng; Wang, Wenchong; Hu, Wenping; Chi, Lifeng
Graphical abstract: Organic complementary inverters driven by surface-grafting conducting polypyrrole electrodes are demonstrated. The inverters show a high operation frequency of about 3.3 kHz, low operational voltage (<8 V), high gain (6–17), low power dissipation (several tens of nW), and large noise margin (>70% ½ V dd ). This work may promote the application of surface-grafting conducting polymer electrode in organic electronics. Highlights: A bottom-up in-situ polymerization strategy is utilized to produce the surface-grafting PPY electrodes. The patterned PPY electrodes may serve as good electrode to efficiently drive organic complementary inverters. The inverter with PPY electrodes exhibits an operation frequency of several kHz. Abstract: Surface-grafting conducting polymer has advantage to circumvent the difficulty in patterning as well as the weak interface adhesion on substrate of the conventional conducting polymer, which would be desirable for its application as electrodes in electronic devices. In this work, the patterned surface-grafting polypyrrole (PPY) is used as electrode, which shows merits such as strong interface adhesion, robustness against solvent treatment, easy scaling-up, and good conductivity. Remarkably, the surface-grafting PPY electrodes can efficiently drive both p-type and n-type organic field-effect transistors. By combining p-/n-type transistors, organic complementary inverters are constructed with PPY electrodes, which exhibit low operational voltage (<8 V), high gain (6–17), and low power dissipation (several tens of nW). The switching voltage is approximately 0.5 V dd with a high noise margin (>70% of 0.5 V dd ). Dynamic switching measurements indicate that the inverter has an operational frequency of about 3.3 kHz. This is the first report on kilohertz organic complementary inverter driven with surface-grafting conducting polymer electrodes. High device performance, together with the facile patternability and other merits, may promote the application of surface-grafting conducting polymer electrode in the field of organic electronics.